Trade Transformation in Pasar Senen 1974-1977: From the Malari Riots to Market Restructuring - Alviana Junita Syaira; Carolina Santi Muji Utami (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
The Malari riots of 15 January 1974 brought about profound changes in the structure of trade and the livelihoods of traders at Pasar Senen, Jakarta. Prior to this event, Pasar Senen functioned as one of the principal centers of trade and distribution, supporting the provision of essential goods for urban communities. The riots resulted in extensive physical destruction of the market, the disruption of trading activities, and significant economic losses for traders. This study aims to analyze the transformation of trading practices at Pasar Senen following the 1974 Malari riots, as well as the policies implemented by the Jakarta Provincial Government in the processes of restructuring and recovery. The research employs a historical method, encompassing the stages of heuristics, source criticism, interpretation, and historiography, utilizing primary sources in the form of contemporary newspapers, including Berita Buana, Sinar Harapan, Merdeka, and Pelita. The findings indicate that recovery policies were not solely focused on the physical rehabilitation of the market but also involved the restructuring of the trade distribution system through trader relocation and the transfer of distribution functions to the Kramat Jati Central Market. These policies led to changes in cost structures and weakened the bargaining position of small scale traders, as reflected in rising operational costs and reduced economic leverage. The post Malari recovery of Pasar Senen reflects a shift in the role of the state in regulating urban trade, with direct implications for the socio economic conditions of traditional market traders.